INFEKSI ENDOPARASIT PADA KUCING DOMESTIK (Felis domesticus) DI PASAR TRADISIONAL KECAMATAN SAWAHAN KOTA SURABAYA - Dyah Widhowati; Rochiman Sasmita; Olan Rahayu Puji Astuti Mussa; Helda Asniyani Benu (VITEK : Bidang Kedokteran Hewan, 2019)
Toxoplasma gondii is an intracellular parasite of the protozoan group and is obligate parasite with definitive host is a cat and other family felidae, Toxoplasma gondii can cause Toxoplasmosis and is categorized as one of zoonotic diseases. This study aims to determine the Toxoplasma gondii infection in domestic cats (Felis domesticus) in the traditional markets of Sawahan sub-district, Surabaya City. This study used a faecal sample of 46 domestic cats in the traditional markets of the Sawahan sub-district consisting of 20 female cats, 10 male cats, and 16 kittens. Then examined at the Laboratory of Parasitology, Faculty of Veterinary Medicine, Wijaya Kusuma University. The examination was carried out by the native method using eosin 2% and the floating method using saturated sugar and observed under a microscope with a magnification of 100x-400x. The results showed there were no cats infected with Toxoplasma gondii but found 3 endoparasites namely Ancylostoma sp 23.9%, Toxocara cati 41.3% and Isospora rivolta 4.3%.